Emerging from the Bibliographic Wilderness: Catalogue Automation in the Bodleian Library, University of Oxford - Burnett, Peter P. (Cataloging & classification quarterly, 2000)
This article provides a history of cataloguing and catalogue automation at the Bodleian Library, Oxford University and includes a description of the Catalogue Support Services within the Cataloguing Division of the Bodleian Technical Services Department. The 1995 decision to migrate to Geac and some subsequent development and implementation is described along with staff training for the cataloguing module. The article includes an assessment of the impact of automation and challenges for the future.